Pengaruh Auditor Eksternal dan Auditor Internal pada Pelaksanaan Good Corporate Governance - Hermawan, Atang (Jurnal Trikonomika, 2010)
Financial performances can show the ficture of successful form of enterprise value for both present and future time. Financial performance can be achieved optimally by the implementation of good corporate governance. Reformation of integrated information systems covering budgeting system, information system, auditing and institutional reformation will yield clean governance. And accountancy will consequently show its maximum role. The purposes of this research is to analyze and learn (1) Correlation of the external and internal auditor, (2) the influence of the external and internal auditor to the implementation of good corporate governance. Research method was descriptive and verificative analyses. The conclusions of the research are as follow (1) a significant correlation of the external and internal auditor, (2) external and internal auditor can influence to implementation of good corporate governance.